Advances in design, simulation and manufacturing III : proceedings of the 3rd International Conference on Design, Simulation, Manufacturing : The Innovation Exchange, DSMIE-2020, June 9-12, 2020, Kharkiv, Ukraine.: proceedings of the 3rd International Conference on Design, Simulation, Manufacturing : The Innovation Exchange, DSMIE-2020, June 9-12, 2020, Kharkiv, Ukraine. Mechanical and chemical engineering / Volume 2, (2020) - Unknown
No abstract available